PERILAKU PERJALANAN PENGGUNA SEPEDA MOTOR UNTUK TUJUAN BEKERJA DI PUSAT KOTA SEMARANG (STUDI KASUS: KORIDOR SEGITIGA EMAS) - Jonathan Suek; Okto Risdianto Manullang (TATALOKA, 2019)
Working activity is one of the subsistence activities with the highest motivation level to travel. In Semarang City, the workplace is still dominant (75.04%) located in the city center, so the city center has a great attraction. It makes the provision of public transportation, such as Trans Semarang has a high service area in the city center. Currently, the Segitiga Emas Corridor has been serviced by 5 bus lines, but workers are still using motorcycles. In city scale, the dependency of motorcycle use reached 79.58% in Semarang City. On the other hand, the value of Trans Semarang loading factor is only 54%. This phenomenon is suspected to occur because of public transport services that have not been in accordance with the user’s travel behavior. Travel behavior can be measured through travel patterns that are formed by scheduling daily activities. Decisions in determining travel patterns are inseparable from the socio-demographic, economic and residential aspects. This study aims to understand the relationship between the travel patterns of workers with these aspects, as well as analyzing predictor variables on understanding the provision of urban mass transportation. The research method used is quantitative approach by using descriptive statistics and multivariate analysis through structural equation model (SEM). The results showed that unmarried workers and workers who do not have children or already do not have children at school age are potential workers who can switch modes to Trans Semarang (49,5%). Therefore, married workers with dual-earners in households, have 1-2 school-age children and small households tend to travel complex and difficult to facilitate by Trans Semarang service. Thus, transport services should be tailored to the characteristics and needs of workers, at least for potential demand to attract new users